Benchmarks of Historical Thinking: First Steps - Peck, Carla; Seixas, Peter (Canadian Journal of Education/Revue canadienne de l'éducation, 2008)
Although historical thinking has been the subject of a substantial body of recent research, few attempts explicitly apply the results on a large scale in North America. This article, a narrative inquiry, examines the first stages of a multi-year, Canada- wide project to reform history education through the development of classroom- based assessments. The study is based on participant-observations, documents gen- erated by the project, and interviews, questionnaires, and correspondence with parti- cipants. The authors find impediments – apparently surmountable – in teachers’ ap- plication of potentially difficult concepts, and in their organizational resistance. Key words: assessment, historical thinking, history education, narrative inquiry Bien que la pensée historique ait été récemment le sujet de nombreuses recherches, peu d’entre elles tentent explicitement d’en appliquer les résultats sur une large échelle en Amérique du Nord. Dans cet article, l’auteur décrit les premières étapes d’un projet canadien de plusieurs années visant à réformer les cours d’histoire en recourant à des évaluations basées sur les classes. L’étude s’appuie sur l’observation des participants, des documents générés par le projet ainsi que des entrevues, des questionnaires et de la correspondance avec les participants. Les auteurs identifient des obstacles – apparemment surmontables – à la mise en application par les enseignants de concepts potentiellement difficiles et notent leur résistance organisa- tionnelle. Mots clés : évaluation, pensée historique, cours d’histoire, recherche descriptive